AN ANALYSIS OF ENTREPRENEURIAL ORIENTATION AMONG WOMAN IN BANGALORE - Harshitha K; Dr. Chidananda H L; Dr. Divya Thankom Varghese (EPRA International Journal of Economic and Business Review(JEBR), 2023)
This study investigates the impact of social support, knowledge, and psychological support on entrepreneurial orientation among women in Bangalore. The sample consists of 257 women entrepreneurs and responses were generated using convenience sampling method through structured questionnaire. The findings revealed significant positive impact of social support orientation (β = .877, p < .001), knowledge (β = .714, p < .001) and psychological support on entrepreneurial orientation. This suggests that women with higher level of support from family, friends’ entrepreneurial communities will show greater interest to start business and individual with entrepreneurial skills, market insights and industry knowledge will demonstrate entrepreneurial tendencies. and indicating that higher levels of support from family, friends, mentors, and entrepreneurial communities contribute to women’s entrepreneurial tendencies. Further, study also confirms that that women with greater self-confidence, self-efficacy, and resilience are more likely to pursue entrepreneurial endeavors. Overall, this study emphasizes the significance of social support, knowledge, and psychological well-being in shaping entrepreneurial orientation among women in Bangalore.